Pengembangan Kurikulum Berbasis Nusantara dan Internasional di PAUD Fastrack Funschool Yogyakarta - Siti Umayah; Suyadi Suyadi (Program Studi Pendidikan Islam Anak Usia Dini, UIN Sunan Ampel Surabaya, 2020)
Early childhood education is a children's educational institution that has the aim of learning to develop children's intelligence by using a variety of innovative learning programs. The purpose of this study was to find out how the development of an archipelago-based and international curriculum program in learning was implemented at Fastrack Funschool Yogyakarta. From the results of research conducted by researchers show that in the learning process applying the archipelago curriculum program uses learning with multiple intelligence methods, in which developing linguistic intelligence, logical mathematical intelligence, spatial visual intelligence, musical intelligence, kinesthetic intelligence, iterpersonal intelligence, intrapersonal intelligence, natural intelligence, and, spiritual intelligence whereas in the international curriculum the learning model of seven habits of successful people includes being a proactive person, setting clear targets, working according to priorities, always thinking of profitable ways, trying to understand and then understanding, creating synergies, and always taking time to improve The ability of these multitude of intelligence and habituation is considered to be very effective in learning in early childhood education institutions at Fastrack Funschool Yogyakarta.